Characterization of new phenolic derivatives in Portuguese propolis by electrospray mass spectroscopy - Falcão, Soraia (2011)
This research outlines an extensive characterization of the phenolic composition of a propolis sample from the northeast of Porto gal. For that, ao ethanolic extract was prepared, fractionated by HPLC and the identification of the phenolic compounds was done by electro spray mass spectrometry in the negative mode. This technical approach allowed the identification of 37 phenolic compounds in the Portoguese propolis sample, including seven that were described for the first time. Two of these new compounds had [M-Hr ions at mlz 403, aod the others had [M-Hr ions at mlz 433, mlz 461, mlz 417, mlz 475, and mlz 565. In general, the molecular weight of these compounds was higher thao the common phenolic compounds of propolis aod their fragmentation pattern suggested that they belong to the flavonoid family probably lioked with a phenylpropanoic acid moiety in the position C5 (mlz 403, 433, 461, 475) and C3 (mlz 403, 417), corresponding to pinocembrio and pinobaoksin derivatives. The ion at mlz 565 seems to be a p-counlaric ester derivative dimer.